Artistic Modernity and the Dialectics of Comedy and Tragedy in Chen Yan’s Novel The Comedy - CUI Qinglei (Frontiers of literary studies in China, 2023)
Chen Yan’s new novel The Comedy is a continuation of his writing of the life and destiny of the artists in The Protagonist. Through shaping characters of the Chou (role of the clown) and describing the joy and sadness experienced by them,his new novel presents the artists’ mixed feelings of sorrow and joy and reveals the crises and dilemmas encountered by traditional art against the background of modernity along with the possibility of transformation and conversion. Like The Protagonist, The Comedy follows Chen Yan’s consistent realistic narrative techniques; unlike the solemn and grand aesthetic style of The Protagonist, however, the new novel develops its narrative with a comic approach more in tune with the characters’ identity and inner spirit and shapes the characters and the story based on the dialectics of comedy and tragedy, thus enriching Chen Yan’s original narrative style and contributing a new aesthetic experience.